The Relationship between organizational culture & rganizational Mathurity of staffs in Isfahan Medical University Hospitals - Sh Hosseini; MH Yarmohamadian; S Ajami (Tehran University of Medical Sciences, 2009)
Background: of this study try to determine the Relationship between organizational culture & organizational Maturity of staffs in Isfahan Medical University Hospitals (IMUHs ). Material and Methods: Three questioners (organizational culture , organizational Maturity) was used for accomplishment of this descriptive & Corelational research.The reliability of These questioners was assest with the cronbach alpha coefficient .this questioners were distribute between 360 employees of IMUHs .Data was analysed by SPSS software. Results: Funding showed that the organizational culture scores of 5 hospitals were average & 6 hospitals were lower than average . The level of organizational Maturity was average . Conclusion: There was a significant relationship between organizational culture & organizational Maturity .Hospital Manager should change their organizational culture in order to increases the level of organizational Maturity .